URGENSI KAIDAH AL URF DALAM MENERAPKAN HUKUM SYARA - Ade Fariz Fahrullah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Habit can influence legal material, proportionally. Islamic law does not position adat as a nonimplicative external factor, but on the contrary, provides accommodation space for adat. This fact, among others, causes Islamic law to be flexible. The character of Islamic law that is accommodative of adat (tradition) is very much in line with the function of Islam as a universal religion (for the whole world).